Association Of Hepcidin (HAMP) Gene Polymorphism And Cytokines, Iron, And Hb Levels In Covid-19 Patients - H. Salem , Mustafa; A. Jabir , Ferdous; A. Jabir , Ferdous (Medical Science Journal for Advance Research, 2022)
Introduction: COVID-19 is a new type of coronavirus that infects humans and causes severe acute respiratory syndrome (SARS). Isolated in Wuhan City, China, in December 2019. Similar to discoveries relating to the coronaviruses that cause severe acute respiratory syndrome (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Levels of cytokines (Interleukin-6, Interleukin-1 β ), iron and hemoglobin changed during COVID-19 disease. Hepcidin is an iron regulatory protein that is encoded by the HAMP gene . Material and Methods : Serum IL-6, IL-1 β , Hepcidin are measured by an ELISA kit and Iron ,UIBC , TIBC are measured by colorimetric methods. The genotyping was done by the ARM-PCR technique with a specific set of primers. Results : The difference in Hb and serum iron levels, UIBC, TIBC, IL-1, IL-6, and Hepcidin conc. between the patient and recovery groups is statistically significant at P≤ 0.05 . No significant difference between the two groups in hepcidin gene polymorphism because of Polymorphisms of the hepcidin gene appeared in the two groups (in most samples). Conclusions: The persons involved in this study are (most of them) heterozygous, and this indicates the presence of the mutation allele in the two groups , and it may be one of the reasons for the deficiency in hepcidin that appeared in this study.